Effect of haptic input on standing balance among individuals with incomplete spinal cord injury. (6th March 2017) - Arora, Tarun; Musselman, Kristin E.; Lanovaz, Joel; Oates, Alison
Highlights: Haptic input in form of light touch can reduce COP sway in people with iSCI. The effect of haptic input is greater in people with more intact UE cutaneous pressure. The effect of haptic input is greater in people with less intact LE proprioception. Abstract: The present study investigated the effect of haptic input via light touch on standing balance of individuals with incomplete spinal cord injury (iSCI). Centre of pressure (COP) measures during standing were assessed in 16 participants with iSCI (13 males; 61.1 ± 19.9 years; C1-L4; AIS C and D) and 13 able-bodied (AB) participants (10 males; 59.4 ± 19.7 years). The effects of light touch (touch/no touch), vision (eyes open/closed), and group (iSCI/AB) on COP measures were assessed using a two-way mixed design MANOVA. Correlations were examined between changes in COP measures with touch (ΔCOP), and clinical measures of cutaneous pressure and proprioception in the upper (UE) and lower (LE) extremities in participants with iSCI. Significant main effects for touch ( p <  0.001), vision ( p <  0.001), and group ( p  = 0.01) for all COP measures were found. There was a significant interaction between vision and group ( p  = 0.01) for a subset of COP measures. With eyes closed, ΔCOP was positively correlated with UE cutaneous pressure sensation and negatively correlated with LE proprioception. Compared with AB adults, individuals with iSCI show a greater increase in postural sway when standing with eyes closed than with eyes open. Individuals with iSCI can use light touch to reduce postural sway, and the effect is greater in those with more intact UE cutaneous pressure sensation and more impaired LE proprioception.